Advancing Die Design and Optimization through the Combination Approach: A Focus on Spring-back Compensation - Agus Dwi Anggono; Waluyo Adi Siswanto; Badrul Omar; Agus Yulianto (International Journal of Mathematical, Engineering and Management Sciences, 2024)
This study explores the geometrical deviations that occur in cold stamping, which are caused by the spring-back effects in elastic metals after forming. The primary aim is to introduce and assess the Combination Approach. This approach seamlessly integrates the Displacement Adjustment and Spring Forward methods for die compensation. This multi-stage process meticulously corrects dimensional errors and effectively reduces spring back through iterative processes. Using the NUMISHEET model, numerical simulations have shown a significant reduction in spring back errors, with up to a 55% reduction achieved with optimized die surfaces after five iterations. The proposed Combination Approach improves the accuracy of die design and contributes significantly to the stamping industry by incorporating established techniques within finite element software. This research broadens the scope of die compensation strategies, creating new opportunities for achieving precise die design in stamping.